Two Fibulae from the Early Iron Age Found out of Context in Eastern Wielkopolska - Kaczmarek, Maciej; Wawrzyniak, Mateusz (Analecta Archaeologica Ressoviensia, 2017)
The paper discusses the non-contextual finds of two bronze fibulae, coming from the Early Iron Age, revealed in eastern Wielkopolska by amateur metal detecting searchers (detectorists). One of them represents an unknown form, morphologically similar to Tłukomy type, whereas the other one (only its bow has been preserved) probably belongs to the Wymysłowo-Wróblewo type, isolated in the items collection as a brooch with a decorative foot (Fusszierfibeln). Both copies are an element to research the relative chronology of the decline of the Hallstatt period and the beginning of the Pre-Roman period in Wielkopolska.